Tools for the genetic manipulation of Zygosaccharomyces rouxii - Pribylova, Lenka; de Montigny, Jacky; Sychrova, Hana (FEMS yeast research, 2007)
A set of tools for the genetic manipulation of the osmotolerant yeast Zygosaccharomyces rouxii was developed. Auxotrophic mutants (ura3 leu2, ura3 ade2, ura3 leu2 ade2) derived from the CBS 732 type strain were prepared. Centromeric and episomal Z. rouxii/Escherichia coli shuttle plasmids with different marker genes (ScURA3, ZrLEU2, ZrADE2) and with multiple cloning sites were constructed, together with a plasmid enabling green fluorescent protein-tagging. A system for repeatable targeted gene deletion in Z. rouxii was established, involving first the integration of a PCR-generated loxP-kanMX-loxP cassette and second the removal of kanMX from the genome using a Z. rouxii plasmid harbouring cre recombinase.
Keywords: Cloning, Molecular; Green Fluorescent Proteins; Plasmids; Molecular Biology; Zygosaccharomyces; metabolické sítě a dráhy; molekulární biologie; sekvenční delece; Genes, Reporter; zelené fluorescenční proteiny; Sequence Deletion; plazmidy; reportérové geny; klonování DNA; Escherichia coli; Metabolic Networks and Pathways; genetické vektory; Mutagenesis, Insertional; Genetic Vectors; inzerční mutageneze